KARAKTERISTIK DAN KINERJA BURUH WANITA PADA GUDANG TEMBAKAU GMIT DI KECAMATAN PANTI KABUPATEN JEMBER - Nurhardjo, Budi (BISMA: Jurnal Bisnis dan Manajemen, 2012)
Particular characteristics will influence individual behavior, both on dailyor job behavior. Individual characteristics can be described by: biographic,personality, perception and attitude. This research was a study about women laborin GMIT tobacco warehouse at Sub District of Panti District of Jember,to know:(1) characteristics; (2) performance and;(3) there was or was not correlationbetween characteristics and performance of women labor. The result were: (1) thecharacteristics of women labor were: 52,8% of them were 16-18 years and 47,2%of them were 19-55 years; 70% were ungraduate from primary school; 82,5%worked for family extra income; 80,02% were married and to fight for family extraincome; 86,68% have husband who worked as labor too; 73,36% have perceptionthat worked as a labor at warehouse more precious than at farm; 50% feelstatisfied in high category and 50% feel statisfied in middle category on routinewages; but on over time work wages 59,94% labor feel unstatisfied and only40,06% feel statisfied in middle category;86,68% labor feel statisfied in middlecategory on general work place condition; (2) performance women labor attobacco warehose were 50% on very high catagory and 50% on high catagory;Just age that had correlation on performance of women labor, although weak butsignificant statistically. The other characteristics also had weak correlatin but notsignificant, even general work place condition had no correlation at all and notsignifikan statistically.